Study about Civil Society and Authoritarian Rule: Ethiopia’s Charities and Societies Law and Experiences of NGO Leaders - Milofsky, Carl; Hunter, Albert (Research Developments in Arts and Social Studies Vol. 1, 2022)
This paper presents an irony, that despite having authoritarian system that has worked to suppress civil society, the authoritarian government of Ethiopia was unable to do this during the period when these data were collected, in 2010. Western theories of civil society argue that the distinctive structures of civil society in different nations are related to historical traditions shaping strong states. In these societies civil society organizations play an important intermediary role between the state and citizens. In Ethiopia, however, the state is weak and despite the coercive efforts of the state, civil society has remained strong. Evidence for this is provided in this paper through interviews of people who led NGOs that were forced to lay off most of their employees after passage and implementation of the Charities and Societies Act in 2009. These respondents argued that despite the coercive power wielded by the state, grass roots democratic organizations were so wide spread, so functionally effective, and so important to the people that they would continue on even if central offices were forced to lay off most of their paid employees. Seven years after these interviews were carried out, claims about the strength of civil society in Ethiopia were borne out in the spring of 2018 as a new democratic government took power in Ethiopia and lifted repressive controls. Civil society is made up of a thatch or vertical and horizontal network relationships that also are tied into government.